Optimising social procurement policy outcomes through cross-sector collaboration in the Australian construction industry. Issue 7 (30th September 2020) - Loosemore, Martin; Denny-Smith, George; Barraket, Jo; Keast, Robyn; Chamberlain, Daniel; Muir, Kristy; Powell, Abigail; Higgon, Dave; Osborne, Jo
Abstract : Purpose: Social procurement policies are an emerging policy instrument being used by governments around the world to leverage infrastructure and construction spending to address intractable social problems in the communities they represent. The relational nature of social procurement policies requires construction firms to develop new collaborative partnerships with organisations from the government, not-for-profit and community sectors. The aim of this paper is to address the paucity of research into the risks and opportunities of entering into these new cross-sector partnerships from the perspectives of the stakeholders involved and how this affects collaborative potential and social value outcomes for intended beneficiaries. Design/methodology/approach: This case study research is based on a unique collaborative intermediary called Connectivity Centre created by an international contractor to coordinate its social procurement strategies. The findings draw on a thematic analysis of qualitative data from focus groups with 35 stakeholders from the construction, government, not-for-profit, social enterprise, education and employment sectors. Findings: Findings indicate that potentially enormous opportunities which social procurement offers are being undermined by stakeholder nervousness about policy design, stability and implementation, poor risk management, information asymmetries, perverse incentives, candidate supply constraints, scepticism, traditional recruitment practices and industry capacity constraints. While these risks can be mitigated through collaborative initiatives like Connectivity Centres, this depends on new "relational" skills, knowledge and competencies which do not currently exist in construction. In conclusion, when social procurement policy requirements are excessive and imposed top-down, with little understanding of the construction industry's compliance capacity, intended social outcomes of these policies are unlikely to be achieved. Originality/value: This research draws on theories of cross-sector collaboration developed in the realm of public sector management to address the lack of research into how the new cross-sector partnerships encouraged by emerging social procurement policies work in the construction industry. Contributing to the emerging literature on cross-sector collaboration, the findings expose the many challenges of working in cross-sector partnerships in highly transitionary project-based environments like construction.